SLOPE STABILITY OF EMBANKMENTS ON SOFT SOIL IMPROVED WITH VERTICAL DRAINS - Kassou, F.; Bouziyane, J. Ben; Ghafiri, A.; Sabihi, A. (Civil Engineering Journal, 2020)
The overloads of structures or embankments built on clayey soft ground are generally applied gradually, respecting a specific phasing. This phasing on construction allows the undrained shear strength of clay increasing over consolidation in order to avoid the risk of collapse during loading. In this work, the undrained shear strength of clay over the consolidation was estimated following SHANSEP method of which parameters proposed by eight researchers have been employed, as well as the slope stability analysis of embankments on soft soils during staged construction. Assessment of factor of safety for slope stability was conducted basing on the Bishop method. Additionally, the variations of undrained shear strength and factor of safety were presented. In order to validate the methods discussed in this study, slope stability analysis of five embankments constructed on clayey soft soils improved by the vertical drain technique in a high-speed railway construction project in Morocco was performed. For these embankments, field measurements about lateral displacement are presented.  It was found that some of the adopted methods is in a good agreement with field measurements. Hence, generalization of these methods to many soft ground cases can be proposed.